Growth Differentiation Factor-15: One of the Missing Links between Psoriasis and Metabolic Syndrome - Essam M. Akl; Nehad A. Fouad; Maram S. Mahmoud; Karem T. Khalil (Indian Dermatology Online Journal)
Background: Psoriasis is a chronic inflammatory condition of the skin that can be related to a variety of other conditions, including cardiovascular disease and metabolic syndrome. Growth differentiation factor-15 (GDF-15) is a cytokine that reacts to cellular stress. GDF-15 serum levels may have clinical uses in a variety of inflammatory and cardiovascular conditions. Objectives: To determine the levels of GDF-15 in the serum of patients with generalized plaque psoriasis (GPP) and its correlation with the metabolic syndrome. Patients and Methods: This case-control study included 50 patients with GPP and 50 age- and sex-matched healthy volunteers as controls. A general examination was performed, with a particular emphasis on measurements of body mass index, circumference of the waist, and blood pressure. Psoriasis severity was assessed using the Psoriasis Area and Severity Index (PASI) score. In addition, laboratory tests, including fasting blood sugar, lipid profile, and serum GDF-15 level measurement, were made. Results: Patients had significantly higher median GDF-15 levels compared to controls (P < 0.001). GDF-15 showed a substantial correlation with both disease duration and PASI score (P < 0.001 for each). GDF-15 levels were considerably greater in participants with metabolic syndrome compared with those without (P = 0.01). Limitation: The relatively small sample size could be a disadvantage and drawback of the study. Conclusion: Serum GDF-15 levels are linked to the severity of psoriasis and the associated metabolic disorders.